Wieser, Doris & Ana Filipa Prata (ed). 2018. Cities of the Lusophone World. Literature, Culture and Urban Transformations. Oxford et al.: Peter Lang - Alexander Altevoigt (apropos [Perspektiven auf die Romania])
Rezension